2021
DOI: 10.2147/ijgm.s291395
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of IL1R1 and IL1R2 Genetic Variants on Rheumatoid Arthritis Risk in the Chinese Han Population: A Case–Control Study

Abstract: Background Rheumatoid arthritis (RA), an autoimmune systemic inflammatory disease, largely resulted from genetic factor. Our purpose was to explore the association for IL1R1 and IL1R2 genetic variants with RA susceptibility in the Chinese Han population. Patients and Methods A total of 508 RA patients and 494 controls were involved in this case–control study; single-nucleotide polymorphisms (SNPs) genotyping was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Another study showed that IL1R2 acts specifically on macrophages as a decoy receptor for IL-1 and is an important regulator of arthritis with an impact on RA risk in Chinese Han population. [23] IL1R2 promotes self-renewal of breast tumor initiating cells and proliferation and invasion of breast cancer cells by binding to and enhancing nuclear ubiquitin-specific protease 15 (USP15) activity. [24] IL1R2 gene polymorphisms and their interactions are associated with the susceptibility to osteoporosis in Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that IL1R2 acts specifically on macrophages as a decoy receptor for IL-1 and is an important regulator of arthritis with an impact on RA risk in Chinese Han population. [23] IL1R2 promotes self-renewal of breast tumor initiating cells and proliferation and invasion of breast cancer cells by binding to and enhancing nuclear ubiquitin-specific protease 15 (USP15) activity. [24] IL1R2 gene polymorphisms and their interactions are associated with the susceptibility to osteoporosis in Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…Both the membrane‐bound and soluble forms of IL1R1 have biological activity, which regulates the inflammatory response by activating and antagonizing cytokine activity. 47 , 48 Studies have demonstrated the association of IL1R1 with autoimmune diseases, including rheumatoid arthritis, 49 as well as cancers such as breast cancer 50 and colorectal cancer, 51 along with inflammatory diseases like inflammatory bowel disease. 52 First of all, our research shows that the expression level of IL1R1 protein is related to the occurrence of allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that MMP9 [347], CBS (cystathionine beta-synthase) [348], IGF2 [349], IGFBP2 [350], HP (haptoglobin) [351], MAPK14 [352], LRG1 [353], LCN2 [354], SBNO2 [355], ITGA1 [356], IL1R2 [357], IL1RN [358], TLR4 [359], IRS2 [360], CORIN (corin, serine peptidase) [361], WNT16 [362], CD80 [363], FASLG (Fas ligand) [364], CXXC5 [365], CNR2 [366], TCF4 [367], PTCH1 [368], TXNIP (thioredoxin interacting protein) [369], TRAF3IP2 [370], ETS1 [371] and ARHGEF3 [372] are strongly associated with osteoporosis. MMP9 [373], S100A12 [374], IGF2 [375], GPR84 [376], SOCS3 [377], CEBPA (CCAAT enhancer binding protein alpha) [378], PGLYRP1 [379], HP (haptoglobin) [380], MMP8 [381], OSM (oncostatin M) [382], TLR5 [383], S100A8 [384], ARG1 [385], S100A9 [386], BCL2A1 [387], IRAK3 [388], ST3GAL4 [389], IL1R1 [390], MAPK14 [391], IL4R [392], PADI4 [393], LCN2 [394], CEBPB (CCAAT enhancer binding protein beta) [395], TSPO (translocator protein) [396], IL18RAP [397], PLAU (plasminogen activator, urokinase) [398], CDA (cytidinedeaminase) [399], SLC11A1 [400], RETN (resistin) [401], GADD45A [402], BCL6 [403], CD55 [404], THBS1 [405], IL1R2 [406], TGFA (transforming growth factor alpha) [407], IL1RN [408], ALDH1A2 [409], SLC8A3 [410], HMGB2 [411], NFIL3 [412], MSRA (methionine sulfoxidereductase A) [413], ITGAM (integrin subunit alpha M) [414], TLR4 [415], SIGLEC9 [416], GRB10 [417]...…”
Section: Discussionmentioning
confidence: 99%